2015
DOI: 10.5455/2320-1770.ijrcog20150420
|View full text |Cite
|
Sign up to set email alerts
|

Study on the acceptance, complications and continuation rate of post-partum family planning using the post placental intrauterine contraceptive device among women delivering at a tertiary care hospital

Abstract: Background: Post placental intrauterine contraceptive device use in India showed that most women were satisfied with their choice of immediate insertion of an IUCD and the rates of complications were relatively low. The large proportion of women accepting the method to limit future childbearing indicates the important place post placental IUCD hold. This study was done to evaluate the acceptance of intrauterine contraceptive device as an immediate family planning method following delivery. The complications as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
5
9
0
Order By: Relevance
“…A higher acceptance rate was also observed among multipara (69.59%) and those who had a desire for future pregnancy after an interval of more than 2 years (75.64%). These findings are similar as results observed by Deshpande et al and Gujju et al 14,17 Present study revealed that there was higher acceptance rate among multipara (69.59%) and those who had a desire for future pregnancy after an interval of more than 2 years (75.64%) this is similar to finding reported by Deshpande et al but in contrary to study conducted by Mishra and by Gautam et al it was seen that there was a higher acceptance in primigravida. 14,18,19 This observation suggests that in present study multi gravida were more receptive to this spacing method of contraception.…”
Section: Discussionsupporting
confidence: 83%
“…A higher acceptance rate was also observed among multipara (69.59%) and those who had a desire for future pregnancy after an interval of more than 2 years (75.64%). These findings are similar as results observed by Deshpande et al and Gujju et al 14,17 Present study revealed that there was higher acceptance rate among multipara (69.59%) and those who had a desire for future pregnancy after an interval of more than 2 years (75.64%) this is similar to finding reported by Deshpande et al but in contrary to study conducted by Mishra and by Gautam et al it was seen that there was a higher acceptance in primigravida. 14,18,19 This observation suggests that in present study multi gravida were more receptive to this spacing method of contraception.…”
Section: Discussionsupporting
confidence: 83%
“…The present study showed that majority of women who accepted PPIUCD had attained secondary education and graduation (51.31%), and only 9% were illiterate; similar recent studies by Kanhere et al (5) and Gujju et al (7) also showed 43% and 32.67% of educated accepting PPIUCD respectively. In the present study insertion of PPIUCD in literate women was high and extremely statistically significant (P<0.0001) as compared to illiterate women.…”
Section: Discussionsupporting
confidence: 61%
“…3 In another study by Gujju et al, the acceptance level of postplacental IUCD was found to be 18.5%. 4 However, the acceptance of postplacental IUCD was much higher (36%) in the study by Kanhere et al 5 After 6 months of follow-up, it was seen that in postplacental group, 4.4% of the women had expulsion of the IUCD whereas in the interval group, 4.1% of women had expulsion. In the study conducted by Lucksom et al, they reported nil expulsion rate in postplacental group versus 5.95% in the interval group.…”
Section: Discussionmentioning
confidence: 86%